If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 34 + -6x = 1 + -7x + 3 Reorder the terms: 34 + 2x + -6x = 1 + -7x + 3 Combine like terms: 2x + -6x = -4x 34 + -4x = 1 + -7x + 3 Reorder the terms: 34 + -4x = 1 + 3 + -7x Combine like terms: 1 + 3 = 4 34 + -4x = 4 + -7x Solving 34 + -4x = 4 + -7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7x' to each side of the equation. 34 + -4x + 7x = 4 + -7x + 7x Combine like terms: -4x + 7x = 3x 34 + 3x = 4 + -7x + 7x Combine like terms: -7x + 7x = 0 34 + 3x = 4 + 0 34 + 3x = 4 Add '-34' to each side of the equation. 34 + -34 + 3x = 4 + -34 Combine like terms: 34 + -34 = 0 0 + 3x = 4 + -34 3x = 4 + -34 Combine like terms: 4 + -34 = -30 3x = -30 Divide each side by '3'. x = -10 Simplifying x = -10
| 9+12p-4=9p+30-2p | | 2/5*6+1=7 | | x^2+16x-4=0 | | 2(9x^2+18x+8)=0 | | 2x-5(x-3)=-4+5x-29 | | 4000(16)=p | | 4x+16=2x+25 | | 3x^2+35x+88= | | 0.75(12x-8)=-18 | | 4a^2+14a-30= | | 6-2(3times-1)=2 | | 13+59n=13 | | 8t^2+5t-75=0 | | 5x^2+39x+60= | | 3(4-6x)+4=2(x+4) | | 8b-24a=-78 | | 8n=-36 | | -152=8(1+4v) | | 15x-142=6x-7 | | -6n=-16 | | 3x^2-4=8 | | y^2+10y-2x=0 | | 28-6x=10x | | 14-9x=74-37x | | 3x^2-4= | | 4+3x-13=12x+5-9x | | 3t^2+16t+16= | | 3(x+5)-12=30 | | 5(y+5)=6(y-3) | | 2(2x-1)-4(3x+1)=2 | | 4x-7-x+8=0 | | 73=-6(r-7)+6(k+5) |